Analysis of Inundation Area as an Impact of Sea Level Rise in Dumai City, Riau Province - Situmorang, Ally Wibowo; Mubarak, Mubarak; Elizal, Elizal (Faculty of Fisheries and Marine, Universitas Riau, 2023)
This research was carried out in December 2021-January 2022 in Dumai City District, Riau Province. The purpose of this study is to determine the rate of sea level rise based on analysis of tide data from 2001-2021 and to predict inundation areas in the next 20 years. This research method is a descriptive survey using remote sensing as an additional tool to show the results. Acquisition needs are in the form of primary data (land use and tide data) and secondary (slope data, elevation, land use, and tide data). These parameters are processed and analysed to describe the extent of the inundation by displaying a map of the City of Dumai. The results showed that the waters of Dumai City have a Formzhal number of 0.5, which means that the water area is classified as a mixed tide, semi-diurnal prevalence, with a sea level rise of 2.003 cm/year. Then, the numbers used to predict the height of sea level rise in the next 20 years are 0.973 m each. Furthermore, sea level height was analyzed to obtain the inundation area for the next 20 years, it turns out that the inundation area each year is 11.89 ha.